Metody pozyskiwania materiałów autobiograficznych do badań nad rodziną - Janiszewski, Ludwik (Wydział Prawa i Administracji UAM, 1989)
In the first part of this article the author presents the phenomena, appearing in a family, for the studies of which autobiographical materials are indispensable. To such phenomena the author includes interpersonal ties (especially emotional, sexual and financial), emotional moods, tensions and conflicts in a family, activities and relations of family members with individuals groups situated outside the family. The above phenomena are the aspects of family life which are usually hidden from the outside observers. Besides, being of intimate and private character, those phenomena should be investigated by means of subtle, qualitative research techniques. In the second part of his article the author discusses types of methods of acquiring autobiographical materials. He distinguishes classical and non-classical methods. To classical methods he includes those where a researcher acquires materials in the form of memoirs, diaries, or letters written by members of a family and expressing their subjective opinions about a given event. To non-classical methods the author includes those applied by contemporary researchers of family life, connected with intensive, multiaspect and system family studies, such as autobiographies told directly to a researcher and recorded on a tape or so- '-called multiplied autobiographies, i.e. life-stories told not by one but by all members of a family.
Methods of acquiring autobiographical materials for family studies